2018
DOI: 10.1093/jxb/ery089
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of strigolactones with abscisic acid during the drought response in rice

Abstract: Both strigolactones (SLs) and abscisic acid (ABA) biosynthetically originate from carotenoids. Considering their common origin, the interaction of these two hormones at the biosynthetic and/or regulatory level may be anticipated. Here we show that, in rice, drought simultaneously induces SL production in the root, and ABA production and the expression of SL biosynthetic genes in the shoot. Under control conditions, the ABA concentration was higher in shoots of the SL biosynthetic rice mutants dwarf10 (d10) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 79 publications
2
89
0
3
Order By: Relevance
“…Moreover, there might be a difference in SL production in monocots and dicots under drought, which could be confirmed in future by comparing SL levels in the monocots and dicots under the same experimental setup. On the other hand, the transcript levels of the SL‐biosynthetic genes D27 and MAX1 ‐homologues Os01g0701400 , Os01g0700900 , Os02g0221900 , and Os06g0565100 were upregulated in rice shoots, as was observed for SlCCD7 and SlCCD8 in the case of tomato (Haider et al, ; Visentin et al, ). These data were in agreement with the detection of increased transcript levels of SL‐biosynthetic genes MAX3 and MAX4 in the leaves of Arabidopsis upon dehydration (C. V. Ha et al, ) and NaCl and mannitol treatments (Lv et al, ), as well as with the upregulation of the SL‐biosynthetic FaD17 gene in the crowns of tall fescue ( Festuca arundinacea ) and the D10 , D17 , and D27 genes in the base of rice stems under drought stress (Table ; Du et al, ; Zhuang et al, ).…”
Section: Sl Production In Plants Under Abiotic Stressesmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, there might be a difference in SL production in monocots and dicots under drought, which could be confirmed in future by comparing SL levels in the monocots and dicots under the same experimental setup. On the other hand, the transcript levels of the SL‐biosynthetic genes D27 and MAX1 ‐homologues Os01g0701400 , Os01g0700900 , Os02g0221900 , and Os06g0565100 were upregulated in rice shoots, as was observed for SlCCD7 and SlCCD8 in the case of tomato (Haider et al, ; Visentin et al, ). These data were in agreement with the detection of increased transcript levels of SL‐biosynthetic genes MAX3 and MAX4 in the leaves of Arabidopsis upon dehydration (C. V. Ha et al, ) and NaCl and mannitol treatments (Lv et al, ), as well as with the upregulation of the SL‐biosynthetic FaD17 gene in the crowns of tall fescue ( Festuca arundinacea ) and the D10 , D17 , and D27 genes in the base of rice stems under drought stress (Table ; Du et al, ; Zhuang et al, ).…”
Section: Sl Production In Plants Under Abiotic Stressesmentioning
confidence: 83%
“…The data obtained from the studies of SL‐deficient mutants clearly indicate a role for SLs in ABA‐mediated stomatal operation, thereby regulating osmotic pressure during plant adaptation to water deficit (Figure ; C. V. Ha et al, ; Liu et al, ; Visentin et al, ). Intriguingly, a recent study in rice reported that the d17/ccd7 mutant plants showed higher ABA accumulation in shoots under drought; however, the authors did neither examine the ABA‐mediated stomatal closure nor the ABA responsiveness of the d17 mutant (Haider et al, ), which would allow us to make a valuable comparison with what was observed in dicot plants, such as Arabidopsis , L. japonicus , and tomato. It is worth mentioning that treatment of broad bean ( Vicia faba ) with GR24 enhanced stomatal closure in a concentration‐dependent manner (Y. Zhang et al, ).…”
Section: Implication Of Sls In Plant Responses and Adaptation To Droumentioning
confidence: 98%
See 1 more Smart Citation
“…Under drought, ABA will be produced in the shoot (Borghi et al 2015) or transported from the root to the shoot (Ko and Helariutta 2017), inducing stomatal closure. Haider et al (2018) found a significant increase in leaf ABA content of rice plants under drought. IAA is important for root and shoot development, and it has been reported that IAA can induce the establishment of arbuscular mycorrhizal fungi (AMF) (Lüdwig-Müller and Güther 2007;Fitze et al 2005).…”
Section: Introductionmentioning
confidence: 90%
“…And there is evidence that the biosynthetic pathways of ABA and SLs are functionally connected. Haider et al . (2018) indicated that SLs interact with ABA during the drought response in rice.…”
Section: Discussionmentioning
confidence: 99%